2012
DOI: 10.1080/10511970.2010.507621
|View full text |Cite
|
Sign up to set email alerts
|

Taking a College Algebra Course: An Approach That Increased Students' Success Rate

Abstract: Florida Atlantic University implemented a number of changes in the College Algebra course in an attempt to improve student success. We summarize these changes, and how they have affected the course. We also discuss possibilities for future improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The data contained students nested within institutions, a clustering effect that is appropriately analyzed with a two-level hierarchical linear model (Goldstein, 2003;Raudenbush & Bryk, 2002) to account for variation in success across institutions. Success was coded "1" and failure was coded "0," and logistic regression was used to model the probability of success.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data contained students nested within institutions, a clustering effect that is appropriately analyzed with a two-level hierarchical linear model (Goldstein, 2003;Raudenbush & Bryk, 2002) to account for variation in success across institutions. Success was coded "1" and failure was coded "0," and logistic regression was used to model the probability of success.…”
Section: Methodsmentioning
confidence: 99%
“…Poor performance in these foundational courses is known to contribute to delayed degree completion or even dropout (Theil, Peterman, & Brown, 2008), among other related impacts. It has been reported that English Composition I (hereinafter, referred to as English Composition) and College Algebra played an integral role in enrollment, persistence, graduation, and success in college (González-Muñiz, Klingler, Moosai, & Raviv, 2012; Tannous & Moore, 2013; Volpe, 2011). Thus, for many freshmen students, success in these baseline courses is critical for the development of higher order critical thinking, future academic attainment, career goals, and labor market success (Adelman, 2006; Johnson & Krase, 2012; Sibulkin & Butler, 2008).…”
mentioning
confidence: 99%
“…One study based on state-level data in Florida found that college readiness for math is associated with the highest math course taken in high school, explaining 28% to 35% of racialized gaps in readiness (Long, Iatarola, & Conger, 2009). Similarly, Gonzalez-Muniz, Klingler, Moosai, and Raviv (2012) discussed how students' numeracy skills developed through a rigorous algebra course, thereby improving their likelihood for college success. Still, these studies have consistently noted sizeable differences in content knowledge and readiness among students who are low income, first generation, Hispanic, and Black.…”
Section: College Readiness Studiesmentioning
confidence: 99%